2023
DOI: 10.3390/jcm12072642
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis of Archival Human Vestibular Schwannoma Tissue from Patients with and without Tinnitus

Abstract: Vestibular schwannoma (VS) is an intracranial tumor that commonly presents with tinnitus and hearing loss. To uncover the molecular mechanisms underlying VS-associated tinnitus, we applied next-generation sequencing (Illumina HiSeq) to formalin-fixed paraffin-embedded archival VS samples from nine patients with tinnitus (VS-Tin) and seven patients without tinnitus (VS-NoTin). Bioinformatic analysis was used to detect differentially expressed genes (DEG; i.e., ≥two-fold change [FC]) while correcting for multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Large tumors may be associated with good hearing function, while some patients with small tumors may suffer from high hearing impairment, suggesting an alternative mechanism besides tumor compression of the nerve [ 32 , 44 , 45 , 46 ]. Recently, it has been shown that NLR family pyrin domain containing 3 (NLRP3) inflammasome activation in VS is correlated with VS-induced hearing loss [ 47 , 48 ]. Tumor necrosis factor (TNF) receptors activate NFκB, which induces increased transcription of NLRP3 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large tumors may be associated with good hearing function, while some patients with small tumors may suffer from high hearing impairment, suggesting an alternative mechanism besides tumor compression of the nerve [ 32 , 44 , 45 , 46 ]. Recently, it has been shown that NLR family pyrin domain containing 3 (NLRP3) inflammasome activation in VS is correlated with VS-induced hearing loss [ 47 , 48 ]. Tumor necrosis factor (TNF) receptors activate NFκB, which induces increased transcription of NLRP3 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these genes have been identified in the transcriptome list of MACC1. Therefore, invasive tumor growth in conjunction with inflammasome activation could be an explanation for an over-proportional hearing loss in some cases with small tumors [ 35 , 47 , 48 , 51 ]. Although the evaluation of invasiveness was out of the scope of this study, MACC1 has been shown to correlate with further invasiveness of tumor cells [ 2 ] and therefore might be relevant for hearing impairment caused by tumor invasiveness.…”
Section: Discussionmentioning
confidence: 99%